Investigating pedagogical potentials of facebook among Centre for Languages and Pre-University Academic Development (CELPAD) learners - Mali, Alaa S.M (Kulliyyah of Education, International Islamic University Malaysia, 2014)
The emergence of technology in social communication has changed not only the way people communicate but also has paved the integration of social communication technology namely social networks in teaching and learning. Educators have explored on ways to infiltrate social network site such as Facebook in learning. The main aim of the study was to investigate the trend of Facebook usage in learning. Secondly, the researcher intended to seek information on the extent of collaboration and information sharing in using Facebook. Thirdly, the researcher attempted to investigate the model of pedagogical potentials of Facebook on student engagement among Centre for Languages and Pre-University Academic Development (CELPAD) students at the International Islamic University, Malaysia (IIUM). The research has been designed with four research questions. The research questions formulated were 1. Does Facebook provide connectivity and social rapport among CELPAD students? 2. To what extent do the CELPAD students collaborate and share information via Facebook? 3. Do the pedagogical potentials of Facebook affect students' engagement in learning English language? 4. To what extent does Facebook help CELPAD students in English language writing? In order to fulfill the purpose of study, adapted questionnaires with 5- Likert scale based on the previous literature were administered to 277 respondents CELPAD students. This research was investigatory in nature, utilizing specifically the quantitative research where cross sectional survey was used as the method of data collection. The data analysis included descriptive statistics to address first and second research questions. Multiple regression analysis was utilized to address the research questions three and four. The items were first content validated by two experts and underwent pilot-study before distributing to respondents. The results of the descriptive analyses show that the majority of the students agreed that Facebook has been moderately used in connectivity and social rapport. Secondly, the results indicate that students use Facebook to collaborate and share information but with low intensity (Overall Mean less than 4.0). The multiple regression analyses show that the model can predict students' engagement using pedagogical potentials of Facebook with total variance explains of 54.7%. The implications of the findings indicate that Facebook can be used effectively in teaching and learning. However, future research in a bigger population is needed to ensure validity of the model to be generalized